2009
DOI: 10.1093/ndt/gfp420
|View full text |Cite
|
Sign up to set email alerts
|

Buttonhole needling of haemodialysis arteriovenous fistulae results in less complications and interventions compared to the rope-ladder technique

Abstract: This study showed that the BH method is a valuable technique with few complications like haematoma, aneurysm formation and the need for interventions. However, the infections induced by the BH method should not be underestimated. This underlines the importance of an aseptic and correct technique of the buttonhole procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
196
2
24

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(229 citation statements)
references
References 10 publications
7
196
2
24
Order By: Relevance
“…Of these studies, eight studies reported total infections (6,7,14,(16)(17)(18)(19)(20), five studies reported systemic infections only (21)(22)(23)(24)(25), and one study reported only local infections (8). There were four RCTs (16,17,19,20) and three observational studies comparing units with different cannulation methods (7,14,23), and the remaining eight studies were observational studies comparing before and after changes (6,8,18,21,22,24,25) (Table 3). Most of the studies were single-center, observational studies, and all were published after 2007; the total number of patients included was greater than 1612 in the majority of the studies.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these studies, eight studies reported total infections (6,7,14,(16)(17)(18)(19)(20), five studies reported systemic infections only (21)(22)(23)(24)(25), and one study reported only local infections (8). There were four RCTs (16,17,19,20) and three observational studies comparing units with different cannulation methods (7,14,23), and the remaining eight studies were observational studies comparing before and after changes (6,8,18,21,22,24,25) (Table 3). Most of the studies were single-center, observational studies, and all were published after 2007; the total number of patients included was greater than 1612 in the majority of the studies.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Most of the studies were single-center, observational studies, and all were published after 2007; the total number of patients included was greater than 1612 in the majority of the studies. The studies were conducted in the United States, Europe, Canada, and Australia; four studies were conducted in an HHD setting (8,14,(22)(23)(24)(25), seven studies were conducted in an in-center hemodialysis setting (6,7,(17)(18)(19)(20)(21), and four studies were conducted in both settings (16). Most of the studies were graded as low level of evidence (Supplemental Table 3 (Figure 3).…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9]15,18 During track formation, perfect insertion of blunt needles was not feasible between the eighth and twelfth cannulation. Thus, the use of blunt needles was reprogrammed from the thirteenth cannulation on, regardless of the etiology of the chronic kidney disease.…”
Section: Resultsmentioning
confidence: 99%